Musical and dramatic songs and their learning (Texas Journal of Multidisciplinary Studies, 2023)
Legacy of teachers, skills and perfection, new creative achievements, new generation, masterpieces of singing and music performance, talent, teacherdisciple tradition, creative approach, Etibor Jalilova, Rahima Mazohidova, folk songs, folk spirit and national songs.